PEMBERDAYAAN PENYULUH AGAMA DALAM PENINGKATAN PELAYANAN KEAGAMAAN KABUPATEN TIMOR TENGAH UTARA PROVINSI NUSA TENGGARA TIMUR - Muchtar Muchtar (Harmoni, 2013)
Religious counseling activities in Indonesian society has a very strategic function. The research problem is as follows : How does implementation of the decision of the Coordinator Minister for Development Monitoring and states apparatus, number: 4/KEP/MK.WASPAN/9/1999? ; What are the efforts that been made by the government in improving the competence of religious counselor?; What is factors that drive and inhibit the religious counselor in carrying out its duties and functions ?; How is the public perception about religious counselor in carrying out its duties and functions? The main source of the data of this research are observation, in-depth interviews, focus group discussion, literature and document review. The research methode used in this study was qualitative research methods.